Choice of ANesthesia for EndoVAScular Treatment of Acute Ischemic Stroke: Protocol for a randomized controlled (CANVAS) trial. Issue 9 (December 2017) - Peng, Yuming; Li, Yan; Jian, Minyu; Liu, Xiaoyuan; Sun, Jian; Jia, Bo; Dong, Jia; Zeng, Min; Lin, Nan; Zhang, Li; Gelb, Adrian W.; Chan, Matthew TV; et al.
Background: Observational studies indicate that the type of anesthesia, local or general, may be associated with the post-procedural neurological function in patients with acute ischemic stroke undergoing endovascular treatment. However, these results need further confirmation, and the causal relationship has not yet been established. Methods: This is a randomized controlled equivalence trial. Permuted block randomization stratified by culprit vessels will be used. Six hundred and forty patients with acute ischemic stroke undergoing endovascular recanalization will be randomized one to one to receive either general anesthesia or local anesthesia. The primary endpoint is the modified Rankin scale at 90 days after endovascular treatment. The secondary endpoints are the peri-procedural mortality and morbidity. Discussion: The study aims to determine the effects of anesthetic choice on neurological outcomes in patients with acute ischemic stroke undergoing intra-arterial recanalization. If the results are positive, the study will indicate that the type of anesthesia does not affect neurological outcome after endovascular treatment. Trial registration: ClinicalTrial.gov identifier: NCT02677415